Strategi Pemasaran untuk Meningkatkan Occupancy Kamar Hotel di Bali melalui Peningkatan Kapasitas SDM yang Bekerja Ada Online Travel Agent - Dadang Hermawan; I Made Darsana; I Gusti Made Sukaarnawa; I Putu Arnawa (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The hotel industry in Bali is facing various challenges that have resulted in low occupancy rates. Some of the main factors contributing to this problem include increasingly fierce competition between hotels, fluctuations in tourist demand due to seasonal and global factors, and the suboptimal utilization of digital marketing channels through Online Travel Agent (OTA) platforms. One of the main causes of this suboptimal utilization of OTAs is the limited capacity of human resources (HR) to effectively manage these platforms. Many HR have not yet mastered digital marketing strategies, are unable to optimally manage hotel listings, and lack the skills to provide superior online customer service. This study aims to formulate an effective marketing strategy by improving HR competency in OTA management. The strategy focuses on digital marketing training, improving customer service quality, and optimizing information and the display of hotel listings on OTA platforms. The method used is a qualitative approach through case studies of several hotels in Bali. Data collection techniques were carried out through in-depth interviews with hotel managers, digital marketing staff, and employees directly involved in OTA management. The results show that improving HR competency through structured training and continuous development has a significant impact on increasing the number of room bookings and occupancy rates. Competent human resources can maximize hotel visibility on OTAs, respond to customer needs more quickly and accurately, and build long-term relationships with them. Integrated marketing strategies with improved human resource quality have proven key to increasing hotel competitiveness, room occupancy, and overall revenue.